Sintesis Biopelumas Dari Minyak Biji Karet: Pengaruh Rasio Molar Minyak Dan Oktanol Serta Suhu Reaksi Terhadap Yield Biopelumas - Susilawati Susilawati; Irdoni Irdoni; Nirwana Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
A lubricant is a liquid that is given between two moving metal objects to reduce the friction. Rubber seed oil is an oil that cannot be consumed because it is poisonous, so it has the potential to be a biolubricant. This research purposes to synthesize biolubricant by using rubber seed oil as raw material and determine the effect of oil and octanol mole ratio and reaction temperature to the biolubricant yield. This research was carried out in several stages: preparation of raw materials including extraction of rubber seed oil by pressing method, then continued by degumming process to purify the oil from the gum. Next, the esterification process to reduce of free fatty acid at the oil. Then, oil will be transesterification process with octanol to make biolubricant with variations of mole ratio oil : octanol was 1:3, 1:5 and 1:7 and variations temperature reaction of 150oC, 170oC and 190oC. This process was did for 6 hours by adding 3% (v/v) oil of NaOCH3 as a catalyst. The highest yield produced was 86,105%. The best biolubricant characteristics were produced at a mol ratio of 1: 5 and reaction temperature of 190°C with a density of 0.832 gr/ml, viscosity index 198.658, flash point 324oC, pour point 5oC and yield 84.357%.Keywords: biolubricants, rubber seed oil, octanol, transesterification